ISCO3 data base, a new tool for doctors and researchers in the area of ozone therapy (Ozone Therapy Global Journal, 2013)
The International Scientific Committee of Ozonetherapy (ISCO3) was created in Viennaon October 8th, 2010. The ISCO3 is an independent board from national andinternational associations or federations of ozone therapy and commercial companies.One of the main purposes of ISCO3 was to develop and maintain a library of allpublished and presented papers on ozone therapy. The library is now a reality andcontains indexed and not indexed papers, books, thesis, historical papers and otherdocuments. For its creation a kind of «brain storm» was generated among the membersand external experts. Finally, the previous experience of Dr. Miika Sallinen and Dr.Jose Baeza was up-dated and reorganized in order to overcome the purpose of ISCO3.The data base is supported by the free software Zotero. Zotero is an easy-to-use toolfor collecting, organizes, cite, and share different research sources. Zotero is anextension for the Firefox web-browser. It runs in its own pane within Firefox, separatelyfrom the web pages. The data base is organized in different files and sub-files for aneasier localization of the scientific content. Topics concerning ozonized oils or waterare separated from ozone therapy. In the same way, inside the file of ozone therapyclinic, pre-clinic, veterinary or other topics are separated.